Pengetahuan Ibu Rumah Tangga (IRT) terhadap Perilaku Pencegahan HIV AIDS di Kota Pekalongan - Putri Andanawarih; Ni’matul Ulya; Ida Baroroh (Jurnal Kebidanan Harapan Ibu Pekalongan, 2026)
HIV/AIDS is an infectious disease with an increasing number of sufferers every year. Efforts made Voluntary Counseling and Testing (VCT) which is a form of counseling aimed at preventing HIV transmission, providing moral support, information, and other support to PLWHA, their families and their environment. The number of HIV cases in Indonesia in 2014 was 22,869 cases, with the most sufferers being housewives reaching 6,539 cases. Housewives exposed to HIV-AIDS are far more numerous than truck drivers, commercial sex workers or workers The purpose of this study was to determine the Knowledge of Housewives (IRT) Regarding HIV AIDS Prevention Behavior in Pekalongan City. This study is a descriptive study with a cross-sectional research design and uses the chi-square statistical test. The results obtained a p value of 0.534 (> 0.05) which means there is no relationship between housewives' knowledge and HIV/AIDS prevention behavior. It is hoped that housewives can continue to increase their knowledge about HIV AIDS prevention and encourage preventive behavior against infectious diseases, especially HIV AIDS